Degree of Practicing the Professional Leadership of the Faculties’ Deans, Their Deputies and Heads of the Scientific Divisions in Al-Qaseem University (Journal Of Educational and Psychological Researches, 2023)
AbstractThe study aims to find out the degree of practicing professional leadership of the faculty’s deans, deputies, and heads of the scientific divisions at Al-Qaseem University. The study has adopted the descriptive analytical method. To achieve the objective of the study, the researcher developed a questionnaire consisting of (45) items distributed to six fields that were applied to a sample of (116) faculty deans, deputies, and the head of division at Al-Qaseem University. The results showed there is a high practicing degree of the study sample individuals of the professional leadership on the questionnaire’s fields as a whole, strategic thinking field came at the first rank, while the innovation, creation fields, leading the individuals, and the resources came at the last rank and at medium practicing degree. Also, the results of the study showed there is no statistically significant difference among means of the study sample individuals’ estimation of practicing a degree of professional leadership in all fields in terms of faculties, except for developing skills of the others field in favor of the scientific faculties. There are statistically significant differences among means of the study sample individuals' estimations for the degree of practicing the professional for all fields in terms of the academic rank in favor of those who have the academic rank (prof). For the experience variable for those with (6) years of experience and more, there are no statistically significant differences between means of the study sample individuals' estimations of the degree of practicing professional leadership for all fields as a whole in terms of the study.